Usos do Acervo Fotográfico do Museu de Comunicação Hipólito José da Costa (2002-2011). - Rodrigues, Ana Ramos (2014)
This thesis aims to analyze the use of the photographic collection of the Museu da Comunicação Hipólito José da Costa (MCHJC), located in the city of Porto Alegre-RS. Created in 1974, said museum aims to save, preserve and disseminate the memory of the media in Rio Grande do Sul This research aims to analyze the uses made by researchers from the photographic collection of the institution to understand how this process occurs construction collective memories through a museum . The study aims to show, before this "memory emergency" we live in contemporary society, such as the uses of a photographic collection, may reflect one of several expressions of "memorial compulsion" as a celebration/remembrance. This research will show that the uses of photographic collection does not occur only on specific dates/ reminiscent of large, but also dates of smaller amplitudes. However, are in great dates they take a larger, as in the case of the fiftieth anniversary of the Campaign Legal (1961), celebration/remembrance in 2011. This year events, productions and publications relating to his 50 years with the use of the photographic collection MCHJC were performed. Constituted by the Archive Piratini Palace, responsible for the official records of the acts of governors between 1947 and 2006 images were produced by the press office of the state government of Rio Grande do Sul. Through the uses of photographic collection in 2011, can is to know the size of this date of celebration / remembrance. Thus, by analyzing the uses of photographic collection was possible to know what were the productions made between 2002 and 2011. Thus, it was observed that there was a major milestone in the quest for the acquis from the implementation of the Projeto Memória Visual de Porto Alegre 1880-1960, conducted in 2005-2006. This project developed actions that encouraged public access to MCHJC.